Analysis gender-responsive budget implementation (Study of the 2019-2023 regional budget of North Sulawesi Province) - Sondakh, Lidya Rilly Eveline; Engka, Daisy S. M.; Walewangko, Een Novritha (Yayasan Widyantara Nawasena Raharja, 2025)
Gender-responsive budgeting is an approach that integrates gender equality and equity objectives into public budgeting processes. This approach encourages local governments to apply a gender perspective in identifying processes, resource allocations, and institutional mechanisms. This study aims to explore the implementation of gender-responsive budgeting in North Sulawesi Province during the 2019–2023 fiscal years. A descriptive qualitative method was employed, utilizing secondary data sources such as policy documents and government reports. The findings reveal that a regional regulation mandating gender-responsive budgeting has been issued to all Local Government Agencies (SKPD) under the North Sulawesi Provincial Government. Several programs aimed at promoting gender equality have been implemented; however, certain budget allocations remain limited and do not fully reflect the principles of gender-responsive budgeting, particularly in terms of commitment to gender transformation as part of regional fiscal innovation. These findings highlight the need for strengthened political commitment and more consistent integration of gender perspectives in regional budgeting practices.